The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1149/1.2120126
|View full text |Cite
|
Sign up to set email alerts
|

On the Preferential Etching of GaAs by  H 2 SO 4 ‐  H 2 O 2 ‐  H 2 O

Abstract: The preferential etching of gallium arsenide in H2SO4‐H2O2‐H2O has been studied. A mechanism for the etching process is discussed drawing on observation by optical and scanning electron microscopy, published results on U H V surface analysis, and surface state models. The etch rates of the revealed planes are related to surface step densities, and the exposure of “equilibrium” step density surfaces is related to the surface migration lengths of probable reactant species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 14 publications
(19 reference statements)
1
23
0
Order By: Relevance
“…This observation agrees with previous works [3][4][5] that concluded that {111}A surfaces are principal slow etching surfaces.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This observation agrees with previous works [3][4][5] that concluded that {111}A surfaces are principal slow etching surfaces.…”
Section: Resultssupporting
confidence: 93%
“…They 2 O system which at some compositions produces polished surfaces remains the most commonly used etchant. Most of these works [4,5,10] have focused on the etched (010) surface and especially on grooves aligned along <110> directions because this surface orientation offers interesting MEMS applications. Some works [3,11] have reported results on localized etchings on other (hhl) substrates covered with mask strips.…”
Section: Introductionmentioning
confidence: 99%
“…The faster etch rate of InP {111}B faces is considered to be due to the full dangling bonds that extend from the phosphorus terminated surface (25,36). Near the pore tips the electric field is sufficiently high to enable substantial tunnelling of carriers (37) and dangling bonds can facilitate a higher etch rate (38).…”
Section: Preferential Etching and The Three-step Charge Transfer Mechmentioning
confidence: 99%
“…One must be careful in routinely assigning this mechanism to any and all pores in etched III-V semiconductors, but the limited and controlled supply of holes in this case is most likely a true explanation of the mechanism of preferential pore growth; no pores are observed in p-type InP electrodes or low doped (~5 u 10 17 cm -3 ) InP anodized in similar KOH solutions (18), and furthermore, a uniform supply of holes at a surface would not result in pore growth or pitting, but electropolishing. A mechanism of chemical etching has been described by MacFayden (38) where it was proposed that chemical etching progresses through the removal of the most loosely bound atoms from the crystal faces. In the case of III-V semiconductors, the {111}B terminating atoms (e.g.…”
Section: Preferential Etching and The Three-step Charge Transfer Mechmentioning
confidence: 99%
“…The control of the membrane thickness and the lateral underetching is of main importance for the device behaviour. Many experimental studies [10,[32][33][34][35] show the panel of 3D shapes which can be realized by changing the anisotropic properties of the baths. The most commonly etching solutions used are composed of sulphuric or phosphoric acid.…”
Section: Wet Etching Surfacesmentioning
confidence: 99%